Analysis on the effect of work-life balance and career development on turnover intention for millennial generations - Purwatiningsih, Erna; Sawitri, Hunik Sri Runing (Management and Entrepreneurship: Trends of Development, 2021)
Millennial generation has unique and different characteristics, become significant human resources which expected to be able to change the condition of an organization to be more productive. Millennial generation employees are more concerned on the aspects of work life balance and self-actualization, such as opportunities to develop their career at work. The fulfillment of work life balance and career development aspects provide the employee of millennial generation last longer within their current jobs and reduce their intention to change an occupation. This research aims to examine various previous literatures study that analyzes about the effect of work life balance and career development on turnover intention of millennial generation. The analysis of this research was done by literature study method that collects previous findings related to the effect of work life balance and career development on turnover intention. The results of the literature review indicated that there is a negative influence on work life balance and career development on turnover intention of the millennial generation of changing their job. It can be concluded that Millennial generation employees are realistic on the fact that they have to move up through the corporate ladder to achieve their career aspirations and more likely to take an active role in their career planning and execution. JEL Classification: O150, P470, J540.